(3GdJSjjQ GdeGdj h GdEOGQI GdeGdjI (B:s (3OQhS hJWHjbGJ (B/s - (3Hf SGSj, GdjGSs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2006)
(3eONd dJSjjQ GdeGdj(B- (3GdJSjjQ GdeGdj hGdHjFI GdeGdjI(B- (3GdJTNjU GdeGdj hGdESJQGJjLj ddeDSSI(B- (3GdJMdjd GdeGdj GdcdGSjcj(B- (3GdJMdjd GdeGdj hGdhXjaj(B- (3JMdjd GdeGdj GdeJMQc(B- (3GdSjGSI GdeGdjI hBdjGJ GJNGP GdbQGQGJ(B- (3fXQjI Gdgjcd GdeGdj(B- (3Shb GdChQGb GdeGdjI(B.s
Keywords: (3GdEOGQI GdeGdjIs; (3GdJSjjQ GdeGdjs